Kompetensi Personality Guru Sekolah Menengah Pertama (SMP) Negeri Kabupaten Aceh Barat - Sy. Rohana Sy. Rohana (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
The teacher’s personality competence (personality) is the important factor to improve education quality. However, in the fact this competence is not prioritized than pedagogical competence and cognitive competence in a teacher training. Moreover, for personality problems is returned to the teachers individually. Basically, the teachers are also a determinant of reciprocation of education, a teacher personal quality is very necessary to become a good personality and authority. In teaching-learning process, the Success indicator of a teacher’s personality and authority can improve students’ achievement. Based on the problems above, the research objectives of this study are 1) to know the general picture of junior high schools (SMP) at west Aceh regency. 2) to know PAIteachers’ personality competence of Junior High Schools (SMP) at west Aceh regency. 3) to know PAI teachers’ authority of Junior High Schools (SMP) at west Aceh regency. 4) to know PAI achievement of Junior High Schools (SMP) at west Aceh regency. This research was a qualitative descriptive analysis research. The instruments which were used to collect the data in this research consist of observation, interview, documentation study, and questionnaire. The subjects of this study are PAI teachers, the principal, the curriculum vice principal and eighth grade students of three Junior High Schools at west Aceh regency. There are: Junior High School (SMP) 3 Meulaboh, Junior High School (SMP) 1 Samatiga, and Junior High School (SMP) 3 Woyla. The result of the research showed that the teachers had Personality Competence, and good authority. Therefore, the first semester students’ achievement in 2013/2014 got high average score of school standard score.